CULTUROLOGICAL APPROACH AS METHODOLOGICAL BASIS OF MATHEMATICAL EDUCATION - Ye. A. Perminov (Russian State Vocational Pedagogical University, 2017)
Introduction. Today, in the era of a mathematization of science and total expansion of digital technologies, mass mathematical education becomes a necessary part of culture of every person. However, there are some serious obstacles to formation and development of general mathematical culture: insufficient understanding of its importance by society and the state; fragmentary-clipconsciousness, emerging among representatives of the younger generation under the influence of the Internet, and preventing formation of a complete picture of the modern world; traditional system of disjointed subjects and courses in school, secondary vocational and high school mathematics education; non-cognitive (automatic) transferring of the approaches, principles, technologies and techniques into training which are not specific in order to master a course. Development of sociological, axiological and especially culturological aspects of mathematical methodology is required for the solution of the urgent problems of methodology in mathematical education.The aim of the publication is to discuss methodological aspects of culturological approach realization in mathematical education.Methodology and research methods. The theoretical scientific methods of the present article involve analysis and synthesis of the content of philosophical, mathematical, pedagogical, methodological literature and normative documents; comparative, culturological and logical types of analysis of mathematical education; systematic, competence-based, practice-oriented and personal-activity metho-dological approaches were used to understand the concept of mathematical education.Results and scientific novelty. The practicability and leading role of culturological approach to promoting mathematical knowledge is proved from historical, philosophical and pedagogical positions. It is stated that objective conceptualization of progressive ideas and new methods of mathematical science and mathematical literacy have the extreme humanitarian importance, since their existence either indirectly or sometimes directly influences quality of life of any person and society in general. The most in-demand, significant and obligatory thematic and methodological components of mathematical education are highlighted: mathematical modeling, discrete mathematics and computing processes. The principle of a cultural conformity and a harmonious combination of the culturological and artfundamentals of mathematical education are emphasized as the basic educational principles, the use of which is capable to improve and raise the level of mathematical culture of the Russian society on a new, higher position.The evidence from this study points towards the idea that effective functioning of the system of mathematical education is impossible without the qualified, well prepared staff who are not only professionals in the subject sphere, but also bearers of high pedagogical culture. Moral and ethical, communicative and individual, and personal components of pedagogical culture of a teacher-mathematician are characterized.Practical significance. The author is convinced that introduction of the proposed concept of mathematical education based on culturological approach to its contents and the organization will help to overcome the disproportions existing today in mathematical education between integration and subject differentiation of a training material, technologization of educational process and preservation of traditional methods of training, fundamentalization of knowledge and competence-based approach to it, etc.Materials of the publication can be useful for future and practising teachers of mathematics and allied sciences, as well as for other categories of the educators engaged in the organization and advance of mathematical education and promotion of mathematical knowledge.